Introducing some secular and feminist theological insights of body into theological conversation - Raymond Potgieter (In die Skriflig, 2015)
Whether the conversation is casual or professional, words such as body, woman, and heart a repart and parcel of community conversation. However, the understanding of the meaning of a specific word such as body may prove to be elusive, vague or alternately take on a complexity often removed from ordinary conversation. Although the insights from Christian feminists have enriched the traditional theological understanding of the word body their insights are not always associated with the general use of the term. A richer understanding of the word results in recapturing the meaning of body, not only for women but also for society’s theological conversation and ‘body-talk’ as a whole.